Peranan Supervisor Pendidikan dalam Meningkatkan Profesionalitas Guru Madrasah Ibitidaiyah Swasta - Wibowo, M Padeli; Hrp, M Faqih Abdillah; Ariesky, Rani Zaskia; Ayumi, Malika; Annisa, Anti; Tania, Fara Nabila; Nasution, Inom (IKAMAS: Manajemen Pendidikan Islam, 2022)
The basic function of supervision is to improve the teaching and learning situation in schools to make it better. A supervisor is a person who is authorized to supervise educational units through efforts to monitor, assess, provide guidance and coaching effectively and efficiently in order to achieve quality educational goals. If supervised If this is implemented properly, the performance improvement of all components of education will be good, the role of the teacher and the responsibility of the teacher as an educative staff will also increase.